Peningkatan Kemampuan Kognitif Materi Kalor Peserta Didik Kelas XI Melalui Implementasi Media Multi Representasi Berbasis Instagram - Darwis, Dian Tari; Tamaela, Elsina Sarah; Limba, Anastasija; Sabandar, Vederico Pitsalitz (Physikos: Journal of Physics and Physics Education, 2022)
One of the learning strategies that can be applied using the e-Learning approaches in physics learning is multi-representational learning by utilizing Instagram social media Instagram is a digital social media platform it many attractive features and designs that can help display and share certain videos and photos. Using Instagram in this research is used as a learning resource in the network. Therefore, the research conducted aims to improve students' cognitive abilities on heat material through Instagram-based multi-representational media. The population in this study were students of XI MIA class at SMA Negeri 7 Ambon, consisting of 45 students. The sample in this study was class XI MIA 2, totaling 22 people obtained using a random sampling technique. Results of research on the initial abilities of students are below the minimum completeness criteria with an average value of 28.90, where 22 (100%) students are in failed the qualification. Then, after being given treatment in the teaching and learning process taking place, an increase was obtained in the final test results with an average value of 80,83. Apart from these results, it is also proven through the N-Gain test where students experience an increase with an average of 0,73 and are included in high qualifications. Based on the research results, it can be concluded that the learning process by utilizing Instagram-based multi-representational media can improve students' cognitive abilities on heat material.